PKM Peningkatan Kuantitas Dan Kualitas Produksi Bakpia Dan Nugget Tempe Melalui Pemanfaatan Teknologi Otomasi Di Desa Bangunharjo - Nugroho, Yohannes Anton; Al Faritsy, Ari Zaqi; Sugiharto, Ari (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
The Community Partnership Program in partnership with the Tani Rahayu Women's Group and the Bakpia Jurug Industry Association have succeeded in helping create economic independence. The results of this program are increased capacity and quality of production of bakpia and tempeh nuggets in the partner group. The implementation of mechanical and automation technology-based tools is able to increase the production capacity of tempe nuggets from 2 kg to 24 kg in a production time of 8 hours. While the implementation of the use of bakpia kumbu processing equipment was able to increase the production of 3 kg to 24 kg in a production time of 8 hours. The utilization of these tools has also been followed by quality assurance training and assistance, so that the quality of the products produced is uniform.